Recent Advances in Polymer Microneedles for Drug Transdermal Delivery: Design Strategies and Applications - Wang, Rui; Jiang, Guohua; Aharodnikau, Uladzislau E.; Yunusov, Khaydar; Sun, Yanfang; Liu, Tianqi; Solomevich, Sergey O. (Macromolecular rapid communications., 2022)
In recent years, transdermal drug delivery based on microneedles (MNs) technology has received extensive attention, which offers a safer and painless alternative to hypodermic needle injections. They can pierce the stratum corneum and deliver drugs to the epidermis and dermis‐structures of skin, showing prominent properties such as minimally invasiveness, bypassing first‐pass metabolism, and can be self‐administered. A range of materials has been used to fabricate MNs, such as silicon, metal, glass, and polymers. Among them, polymer MNs have gained increasing attention from pharmaceutical and cosmetic companies as one of the promising drug delivery methods. MN products have recently become available on the market, and some of them are under evaluation for efficacy and safety. This paper focuses on the current state of polymer MNs in drug transdermal delivery. The materials and methods for the fabrication of polymer MNs and their drug administration are described. The recent progress of polymer MNs for treatment of cancer, vaccine delivery, blood glucose regulation, androgenetic alopecia, obesity, tissue healing, myocardial infarction, and gout are reviewed. The challenges of MNs technology are summarized and the future development trend of MNs is also prospected. The transdermal drug delivery based on microneedles (MNs) technology offers a safer and painless alternative to hypodermic needle injection. In this review, the design and fabrication principles for polymer MNs are introduced. The potential applications of polymer MNs for cancer, vaccine, diabetes, obesity, myocardial infarction (MI), and gout are demonstrated. The remaining challenges of polymer MNs are discussed.